Assess the Effectiveness of Planned Teaching Program on Knowledge and Attitude Regarding Prevention of Urinary Tract Infection among Adolescent Girls in Selected School of Bhabhar City - R, Nikhila; Varghese, Jibin; Josh, Payal; Damor, Mitesh; Chauhan, Chetan; Bhiladiya, Kalpana (International Journal of Nursing Research, 2024)
Aim: The aim of this study was to evaluate the effectiveness of planned teaching program on knowledge and attitude regarding prevention of urinary tract infection among adolescent girls. Materials and Methods: Underdeveloped nations have many urinary tract infections. Adolescent girls are more likely than boys to have it. Urinary tract infections occur in the urinary tract. The urinary tract includes the bladder, kidney, ureter, and urethra. UTIs can be caused by any urinary pathogen, with or without symptoms. Colon-dwelling Escherichia coli strains cause 80% of UTIs. Other microorganisms can cause disease. Although healthy, this stage of life nonetheless has many deaths, sicknesses, and injuries. Most of this is avoidable or treatable. Pre-test, post-test, and control group designs for quasi-experiments were modified. Adolescent girls participated in the study on preventing urinary tract infections. Data were collected using demographic characteristics and 40 samples were chosen using non-probability purposive sampling, self-administered knowledge questionnaire, and modified Likert scale. Results: The study findings showed that Planned Urinary Tract Infection Prevention Education Program was significantly effective in improving teenage girls’ attitudes and knowledge. Information base and outlook of girls regarding urinary tract infection and its prevention are improved. Conclusion: According to the study’s findings, planned teaching programs greatly improved the knowledge and attitudes of adolescent girls, regarding prevention urinary tract infection.